Efek Obat Antituberkulosis Fase Intensif dan Konsumsi Purin Terhadap Kadar Asam Urat Pasien Tuberkulosis - Mustaming Mustaming (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
ABSTRACT A high prevalence of TB requires serious treatment with Anti-Tuberculosis Therapy, but the side effects can gain uric acid levels. This study aimed to analyze the effects of intensive phase therapy and high purine consumption patterns with uric acid levels in TB patients with Anti-Tuberculosis Therapy. This research was an analytic study using a prospective cohort design. The population was all tuberculosis patients who received Anti-Tuberculosis Therapy at several Public Health Centers in Samarinda. The sampling technique used consecutive sampling approach. The respondents were selected according to the inclusion criteria and had signed the informed consent. Furthermore, the venous blood was measured to know the levels of the uric acid pre-test. The measurements of uric acid levels post-test were carried out after undergoing Anti-Tuberculosis Therapy for 2 months and filling out the FFQ questionnaire to determine the patterns of high purine consumption. The collected data was analyzed using a t-paired and a one-way anova test. T-Paired test results exhibited that there were increasing trend in the average uric acid levels after following Anti-Tuberculosis Therapy in an intensive phase of 2.53 mg / dL (39.78%) with p-value <0.001. Besides, the one way anova test results showed that the average difference in uric acid levels in respondents who consumed high purine 4-6 times/week was 3.16 mg / dL and was higher than respondents who never consumed high purine or those who consumed high purine 1-3 times/week with a p-value <0.001. An average increase in uric acid levels in TB patients after undergoing the intensive phase of Anti-Tuberculosis Therapy for 2 months with a pyrazinamide and ethambutol regimen and an increase in uric acid levels was higher compared to respondents who consumed high purine. Keywords: uric acid level, high purine consumption, intensive phase